Extensive Coverage of Marine Mineral Concretions Revealed in Shallow Shelf Sea Areas - Kaikkonen, Laura; Virtanen, Elina A.; Kostamo, Kirsi; Lappalainen, Juho; Kotilainen, Aarno T. (Frontiers in Marine Science, 2019)
Ferromanganese (FeMn) concretions are mineral precipitates found on soft sediment seafloors both in the deep sea and coastal sea areas. These mineral deposits potentially form a three-dimensional habitat for marine organisms, and contain minerals targeted by an emerging seabed mining industry. While FeMn concretions are known to occur abundantly in coastal sea areas, specific information on their spatial distribution and significance for marine ecosystems is lacking. Here, we examine the distribution of FeMn concretions in Finnish marine areas. Drawing on an extensive dataset of 140,000 sites visited by the Finnish Inventory Programme for the Underwater Marine Environment (VELMU), we examine the occurrence of FeMn concretions from seabed mapping and use spatial distribution modelling techniques to estimate the potential coverage of FeMn concretions. Using seafloor characteristics and hydrographical conditions as predictor variables, we demonstrate that the extent of seafloors covered by concretions in the northern Baltic Sea is larger than anticipated, as concretions were found at ~7000 sites, and were projected to occur on over 11 % of the Finnish sea areas. These results provide new insights into seafloor complexity in coastal sea areas, and further enable examining the ecological role and resource potential of seabed mineral concretions.